A technology management system for the development of single-task construction robots. Issue 1 (6th January 2020) - Linner, Thomas; Pan, Wen; Hu, Rongbo; Zhao, Charlie; Iturralde, Kepa; Taghavi, Meysam; Trummer, Julian; Schlandt, Marcel; Bock, Thomas
Abstract : Purpose: Because of the sharply growing interest worldwide of "hard" physical-mechanical robot systems for the execution of on-site construction tasks [i.e. single-task construction robots (STCRs)], the purpose of this study is to equip development projects with a systematic design-management system model that allows to integrate the different needs and aims of stakeholders. Design/methodology/approach: This paper proposes a STCR-technology management system (STCR-TMS) for the complete development cycle of STCR designs. The STCR-TMS is based on established principles from systems engineering and management and STCR-specific activities developed and tested by the authors as standalone elements in previous research work. Findings: The application of the STCR-TMS revealed the practicability of the method and the underlying concepts to provide practical guidance for the development process. Additional findings indicate that the method is sufficiently generic and flexible for application to different types of robots and indifferent world regions. This research has also shown that key activities need to be addressed to increase the practicability of the STCR-TMS. Originality/value: A unique characteristic of this method is the evolution with each utilization cycle. In addition, individual elements are interchangeable and can be adapted based on external circumstances. These properties allow the TMS to be applied to other fields in construction robotics. With the progression of the verification and validation of the method, know-how and certain elements can be fed into standardization activities (e.g. establishing a management system standard).